PENGARUH METODE KINDNESS TERADAP HASIL BELAJAR MATEMATIKA MATERI MEMBANDINGKAN DAN MENGURUTKAN BILANGAN SISWA KELAS II MI NANGELA KABUPATEN TASIKMALAYA - Nina Yuningsih; Yuningsih, Nina Yuningsih; Lidya Sri Kartini (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study was motivated by the low ability of students to understand mathematical concepts, particularly in the topic of comparing and ordering numbers, thereby highlighting the need for innovative teaching methods that are both effective and engaging. The purpose of this research was to analyze the effect of applying the Kindness method on the mathematics learning outcomes of second-grade students at MI Nangela, Tasikmalaya Regency. The study employed a quantitative approach with a pre-experimental one-group pretest-posttest design, involving 26 students as the sample. Data were collected through pretest and posttest assessments, and analyzed using the Shapiro-Wilk normality test and the Mann-Whitney hypothesis test. The findings revealed an increase in the students’ mean scores from 47.7 on the pretest to 78.85 on the posttest, with a significance value of 0.000 < 0.05, indicating a significant difference between learning outcomes before and after the intervention. These results demonstrate that the Kindness method has a positive impact on improving students’ comprehension and motivation in learning mathematics. Therefore, the implementation of the Kindness method can serve as an effective strategy for teachers to create a supportive classroom environment, foster empathy and collaboration among students, and ultimately enhance academic achievement at the elementary school level.